2006
DOI: 10.1159/000090597
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Biogenetic Temperament and Character and Psychopathology in Adolescents

Abstract: Background: This study was conducted to investigate the relationship between patterns of temperament and character and self-reported psychopathology in adolescents from the community. Sampling and Methods: The Junior Temperament and Character Inventory (JTCI) and Youth Self-Report (YSR) instruments were administered to 623 Korean middle school students (boys/girls = 331/292; age = 13.3 ± 0.9 years old). Multiple linear regression analyses were used to evaluate the relationship between temperament and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
5
11
0
1
Order By: Relevance
“…Harm avoidance was positively correlated with internalized problems. This is consistent with the results of previous reports [7,12,24,26,28,38]. HA and NS were the only dimensions positively correlated with CBCL subscores.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Harm avoidance was positively correlated with internalized problems. This is consistent with the results of previous reports [7,12,24,26,28,38]. HA and NS were the only dimensions positively correlated with CBCL subscores.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, further investigations of the biopsychosocial model of personality, with assessments specifically validated in the pediatric population were necessary. Moreover, because of evidence showing the TCI had discriminative power for psychopathological conditions and that some dimensions may differentiate broad categories of disorders, [11,12,42] correlations between the dimensions of JTCI and clinical symptoms of psychopathology needed further investigation [21,28,30,40,43].…”
Section: Introductionmentioning
confidence: 99%
“…The association with the Sensation Seeking subscale of the UPPS (which includes a shortened adaptation of two of the four subscales of Zuckerman’s SSS) was negligible (d'Acremont and Van der Linden, 2007). More broadly, novelty seeking has been consistently associated with the externalizing dimensions and not with the internalizing dimensions of Achenbach’s Scales, including the anxious/depressed subscale (Asch et al, 2009, Copeland et al, 2004, Kim et al, 2006, Kuo et al, 2004). The replicated finding that high levels of novelty seeking in adolescence are associated with both externalizing disorders and suicide risk has led investigators to speculate that adolescents who attempt suicide “may have a mixed affective–behavioural psychopathology… [and] may occupy a midposition between depressive adolescents and those suffering from conduct disorder pathology with regard to character dimensions” (Csorba et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…High self-transcendence is linked to NSSI in adolescents [20] and to BPD in adults [14]. Low reward dependence is linked to internalizing symptoms like depression and anxiety [23], but no association has been found between reward dependence and NSSI [20], nor between reward dependence and self-harm behavior [21, 22]. Kaess et al [18] found lower reward dependence in adolescents with BPD than in clinical and healthy controls.…”
Section: Introductionmentioning
confidence: 99%